Fukugoukakujoshi ~wo moto ni shite dan ~ni motodzuite dalam Kalimat Bahasa Jepang: Menelisik Jenis Nomina, Verba, dan Genre Kalimat - Lubis, Sarah Aini Mahdiyyah; Mulya, Komara; Ristiawati, Tia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
This research aims to determine the nouns, verbs, and sentence genres contained in Japanese sentences that contained fukugoukakujoshi of ~wo moto ni shite and ~ni motodzuite. This was conducted  due to the similar meaning between fukugoukakujoshi ~wo moto ni shite and ~ni motodzuite when translated into Indonesian, which is "based on".  Nevertheless, each word essentially has its own differences. This research uses a qualitative descriptive method with data collection techniques in the form of note-taking techniques, and direct-elements divide analysis technique based on experts’ theories. The used theories are noun type theory, verb type theory, phrase theory, and sentence genre seen from the theory of grammatical categories in the predicate. Based on the analysis results, the nouns, verbs, and sentence genres in Japanese sentences containing fukugoukakujoshi ~wo moto ni shite and ~ni motodzuite have similarities and differences.